Age-related cerebral white matter disease (Leukoaraiosis): A review - Grueter, B; Schulz, U (2012)
With the availability of improved brain imaging techniques, the high prevalence and clinical importance of cerebral small vessel disease have been increasingly recognised in recent years. As age is one of the most important risk factors for this condition, its prevalence is set to rise further as populations age. This may lead to an increase in the clinical consequences of white matter disease, namely cognitive decline, decreased mobility and increased stroke risk. Given the impact this will have on individuals and on healthcare systems, knowledge of the risk factors for small vessel disease, its prevention and its treatment is becoming more important. Although a lot of data are now available on the epidemiology, risk factors, clinical consequences and prognosis of leukoaraiosis, some of this information is conflicting. In this review, we summarise the current literature on cerebral small vessel disease, with an emphasis on its clinical aspects.